A structural and functional perspective of alphavirus replication and assembly. (September 2009) - Jose, Joyce; Snyder, Jonathan E; Kuhn, Richard J
Alphaviruses are small, spherical, enveloped, positive-sense ssRNA viruses responsible for a considerable number of human and animal diseases. Alphavirus members include Chikungunya virus, Sindbis virus, Semliki Forest virus, the western, eastern and Venezuelan equine encephalitis viruses, and the Ross River virus. Alphaviruses can cause arthritic diseases and encephalitis in humans and animals and continue to be a worldwide threat. The viruses are transmitted by blood-sucking arthropods, and replicate in both arthropod and vertebrate hosts. Alphaviruses form spherical particles (65––70 nm in diameter) with icosahedral symmetry and a triangulation number of four. The icosahedral structures of alphaviruses have been defined to very high resolutions by cryo-electron microscopy and crystallographic studies. In this review, we summarize the major events in alphavirus infection: entry, replication, assembly and budding. We focus on data acquired from structural and functional studies of the alphaviruses. These structural and functional data provide a broader perspective of the virus lifecycle and structure, and allow additional insight into these important viruses.